SHORT-VIDEO EEG IN DIAGNOSING NON-EPILEPTIC ATTACK DISORDER. Issue 10 (9th September 2014) - Pettigrew, Katie; Morrison, Ian
Abstract : Background: Non-epileptic attack disorder (NEAD) and epileptic seizures are often hard to differentiate clinically. However accurate diagnosis is essential for the optimum outcome for the patient. Diagnosis often requires inpatient video telemetry, which is both time consuming and financially constraining. Short video electroencephalography (SV-EEG) with provocation has been described previously and was shown to be a useful diagnostic tool in other specialist centres in the United Kingdom. Objective: To determine the usefulness of SV-EEG in the diagnosis of NEAD in a University teaching hospital with no previous SV-EEG experience. Method: Review of medical notes of 35 patients who underwent SV-EEG in Ninewells Hospital between September 2011 and October 2013. Results: A positive SV-EEG supporting a diagnosis of NEAD occurred in 57.1% of patients (n=20). No attack or an atypical attack resulting in an inconclusive SV-EEG occurred in 42.9% of patients (n=15). Conclusion: The positive rates of attacks from SV-EEG were comparable to previously published results and show that SV-EEG is easily implemented in centres with no previous experience of the technique.